The Function of the Family Environment to Improve the Understanding of Islam in Students at State Elementary School 6 Katobu, Muna Regency - Darsimon Darsimon; L. Irian; La Adi; Al Azhar; Kafarun Kafarun (International Journal on Advanced Science, Education, and Religion, 2026)
Islamic religious understanding among elementary school students is a fundamental aspect in the formation of religious character, influenced by various factors, one of which is the family environment as the first education for children. This study aims to analyze the influence of the family environment on the Islamic religious understanding of students at Katobu 6th State Elementary School, Muna Regency. This study used a quantitative approach with a correlational research type, where data were collected through a Likert-scale-based questionnaire administered to the entire population of 47 students. Data analysis techniques included validity, reliability, normality, linearity, Pearson correlation, and simple linear regression tests with the help of statistical software. The results of the study showed a positive and significant relationship between the family environment and students' Islamic religious understanding, where the quality of the family environment contributed to improving students' religious understanding. These findings indicate that worship practices within the family, parental support, and a religious atmosphere at home play an important role in shaping students' Islamic knowledge, attitudes, and behavior. This study contributes to strengthening the role of the family as a primary factor in Islamic religious education and serves as a basis for developing educational strategies that involve synergy between families and schools.